Kepuasan Kerja Sebagai Pemediasi Pada Pengaruh Leader Member Exchange dan Pemberdayaan Terhadap Kinerja - Upik Handayani; Euis Soliha (Ikatan Sarjana Ekonomi Indonesia Cabang Semarang, 2020)
Good governance is an understanding or basis for the accountability of performance of government agencies. Good governance has a meaning as good management or utilization which is expected to be a good performance achievement. Referring to the phenomenon that there is a decrease in performance in the East Semarang Subdistrict in Semarang City and there are still differences in the results of previous research on Member Exchange Leaders and Empowerment with its effect on performance, the research problem formulated is